1994
DOI: 10.1046/j.1365-2648.1994.20040597.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and issues of control among elderly people in health care settings

Abstract: This descriptive study investigated the relationship between both demographic characteristics and type of health care setting and elderly people's attributions for control, functional status, mood, type of helplessness, and perception of self-efficacy. Results of the study demonstrate that elderly people in long-term care settings are more vulnerable to experiencing learned helplessness and depression than elderly people in acute or rehabilitation settings. The findings indicate that the critical period for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…Thus, power components for medication management could be determined through measures such as the MMSE (cognitive limitations), assessment of functional capacity using measures of activities of daily living (ADL) (movement abilities), assessment of ability to perform instrumental ADL (movement abilities and cognitive limitations), and surrogate measures of motivation including depression or prolonged institutionalization. Depression and prolonged institutionalization have been shown to be associated with apathy in older adults (Barder, Slimmer, & LeSage, 1994;Resnick, Zimmerman, Magaziner, & Aldelman, 1998). Finally, age, sex, number of medications, education (resource availability), and number of medical conditions (health state) would be considered basic conditioning factors, as each would affect older adults' self-care agency, as well as therapeutic self-care demand.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…Thus, power components for medication management could be determined through measures such as the MMSE (cognitive limitations), assessment of functional capacity using measures of activities of daily living (ADL) (movement abilities), assessment of ability to perform instrumental ADL (movement abilities and cognitive limitations), and surrogate measures of motivation including depression or prolonged institutionalization. Depression and prolonged institutionalization have been shown to be associated with apathy in older adults (Barder, Slimmer, & LeSage, 1994;Resnick, Zimmerman, Magaziner, & Aldelman, 1998). Finally, age, sex, number of medications, education (resource availability), and number of medical conditions (health state) would be considered basic conditioning factors, as each would affect older adults' self-care agency, as well as therapeutic self-care demand.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…[11][12][13] The studies on humans across the life span suggested four common themes in learned helplessness in humans. These are summarized in Table 1. 1.…”
Section: Human Research On Learned Helplessnessmentioning
confidence: 99%
“…[11][12][13] In addition, specific studies have reported on the association between helplessness or learned helplessness in patients with arthritis, 14,15 ischemic heart disease, 16 and progressive supra-nuclear palsy. 17 Although some of these studies have not followed Seligman's conceptualization of learned helplessness fully, taken as a whole, the published findings [11][12][13][14][15][16][17] establish the presence of learned helplessness in some elderly and that the stance of learned helplessness appears to remain stable across the life span. 18 Although alternative explanations for learned helplessness have been put forward, 9,18 Seligman's cognitive psychological theory has remained the dominant model for understanding learned helplessness with frequent accompanying dysphoria and depression.…”
Section: No Task Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…It may well be that the less restrictive, home-like atmosphere of the assisted living setting influenced participants' responses to these questions. It has been demonstrated that maintaining a perceived sense of control and choice is a major factor in preventing depression and learned helplessness among residents in long-term care facilities (Barder, Slimmer, & Lesage, 1994;Foy & Mitchell, 1990;Langer & Rodin, 1976;Rodin, 1986).…”
Section: Journal Of Housing For the Elderlymentioning
confidence: 99%